Integrated Innovative Assessment Method Through Case Study - Dolly, Paul Carlo (2022)
There is a large body of research that shows a strong impact of different types of assessment on learners learning outcomes. Evidence on different approaches indicates that assessment may support or diminish learners’ motivation and performance depending on how it is designed, implemented, and used. How do educators incorporate and integrate the assessment methods holistically as ways and an opportunity for reflective learning, demonstrating the learner’s thinking, and measuring the learning outcomes (CLOs)? Through case study as an assessment method, the learners have an opportunity to reflect on and bespeak their thinking and lead them towards a better understanding of the concept. Considering the philosophy of teaching and learning, the application and integration of transformative teaching practice and innovative assessment methods into the SSS2053 Counselling Skills turns out the affirmative outcomes and compelling implications towards the learners’ learning.